A comparative analysis on housing policies in Turkey and Lithuania - Yetgin, Feuzullah; Lepkova, Natalija (International Journal of Strategic Property Management, 2010)
The housing sector is a very important sector in the national economy worldwide. The greater importance of the housing sector is broadly defined, to include financing, upgrading, repairs, management, valuation, taxation and population. The article presents a comparative analysis on housing policies in Turkey and Lithuania. The housing strategies – their differences and similarities – of Turkey and Lithuania are presented in the article. Strategic principles and preferences of housing are analysed in the countries under investigation. Some economic aspects are underlined. The policies of social housing of investigated countries are presented. The housing problems of both analysed countries are described. Special attention is paid to sustainable housing and social cohesion in housing. First published online: 18 Oct 2010